Justice Theory Approach To Patient Registration Using Mobile Health In The Hospital - karim, Rindi karim; Merlin Abd.Rahman (International Journal of Law and Legal Ethics, 2025)
This research aims to determine the effectiveness of the use of the Mobile Jaminan Kesehatan Nasional, known as the National Health Insurance (Mobile JKN) application, in the process of registering for health services at the hospital, and to assess the fairness of access to these services based on the approach of justice theory. The research was conducted at Toto Kabila Regional Hospital with a descriptive qualitative approach and phenomenological research method. Data collection techniques were carried out through interviews and the distribution of questionnaires to patients who used the Mobile JKN service. The research results showed that the Mobile JKN application provides convenience for some patients, especially in terms of time efficiency and queue reduction. However, several obstacles were found, such as registration difficulties, network disruptions, and low digital literacy among certain communities. Based on the theory of justice (distributive, communicative, legalist, and vindicative), it was found that access to services through this application was not completely fair and equitable, especially for people who live in remote areas or do not have access to technology. Thus, it is important to increase digital education and better network infrastructure support to ensure equal distribution of Mobile JKN services across all levels of society.